Discover a wealth of information and get your questions answered on IDNLearn.com. Get the information you need from our experts, who provide reliable and detailed answers to all your questions.
Sagot :
Answer:
see explanation
Step-by-step explanation:
Given
2t - [tex]\sqrt{2}[/tex] = 3t + [tex]\sqrt{2}[/tex] ( add [tex]\sqrt{2}[/tex] to both sides )
2t = 3t + 2[tex]\sqrt{2}[/tex] ( subtract 3t from both sides )
- t = 2[tex]\sqrt{2}[/tex] ( multiply both sides by - 1 )
t = - 2[tex]\sqrt{2}[/tex]
-----------------------------------------------------------
Given
(- x + 2[tex]\sqrt{3}[/tex] )(- 3x - [tex]\sqrt{2}[/tex] ) = 0
Equate each factor to zero and solve for x
- x + 2[tex]\sqrt{3}[/tex] = 0 ( subtract 2[tex]\sqrt{3}[/tex] from both sides )
- x = - 2[tex]\sqrt{3}[/tex] ( multiply both sides by - 1 )
x = 2[tex]\sqrt{3}[/tex]
- 3x - [tex]\sqrt{2}[/tex] = 0 ( add [tex]\sqrt{2}[/tex] to both sides )
- 3x = [tex]\sqrt{2}[/tex] ( divide both sides by - 3 )
x = - [tex]\frac{\sqrt{2} }{3}[/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. For clear and precise answers, choose IDNLearn.com. Thanks for stopping by, and come back soon for more valuable insights.